PENGARUH KERAGAMAN PRODUK DAN LOKASI PENJUALAN TERHADAP KEPUASAN KONSUMEN PADA WARUNG MASITAH - Suyono, Agus; Ernawati, Sri (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine (1) whether there is an influence of product diversity on consumer decisions at Masita stalls (2) whether there is an influence of the influence of sales location on consumer decisions at Masita stalls (3) whether or not there is an influence of the influence of product diversity and sales location on consumer decisions. at Masita's shop. The type of research in this study is associative. This research was carried out at the Masita stall, which targeted consumers who had visited the Masita stall. The sampling technique used is purposive sampling with 60 respondents. The data analysis technique used is validity test, reliability test, classical assumption test, multiple linear regression, coefficient of determination analysis test, correlation coefficient, partial test and simultaneous test. Based on the results of the study, it is shown that (1) the product diversity variable has an effect on consumer satisfaction at the Masita stall. (2) the sales location variable has no effect on consumer satisfaction at the Masita stall. (3) variable product diversity and sales locations have an effect on consumer satisfaction at the Masita stall